DERAJAT INFEKSI DAN PREVALENSI EKTOPARASIT PADA IKAN MAS (Cyprinus carpio) DI KABUPATEN BATANG - Linayati Linayati; Tri Yusufi Mardiana; Nur Fadhilah Adimahsyaf; Muhammad Zulkham Yahya; Tristiana Yuniarti (Universitas Mataram, 2024)
Disease attack is one of the obstacles in aquaculture that can cause a decrease in productivity. Fish diseases can be caused by parasites both endoparasites and ectoparasites. The purpose of this study was to determine the type, prevalence, and intensity of ectoparasites in carp cultivated in ponds at the Fish Seed Center in Batang Regency, Central Java. The method used in the study was the survey method. The samples taken were 30 fish. Data were analyzed descriptively quantitatively. The results showed that the type of parasite found in carp was Argulus sp. with an infection rate of 10.7 individuals/head and a prevalence of 67%. The degree of infection is categorized as moderate and the prevalence is categorized as very frequent infection.